Utilization of Social Media and Online Shop Applications to Increase the Income of Traders Around Lake Toba - Daulay, Wardiyah; Nasution, Mahnum Lailan; Boru Tarigan, Juliati (Talenta Publisher, 2022)
Trading has traditionally experienced a decline in sales turnover. For this reason, other efforts are needed to increase sales by utilizing social media and online shop applications. One of the things that support tourism income is the sale of souvenirs typical of Lake Toba. Unfortunately, from the survey results, the sellers are only limited to selling goods in the store without exposing the goods they sell to the internet. So it is necessary to increase the knowledge of traders to help through community service activities to improve the economic status of the community and region. Problem solving can be done by creating a platform as a promotional platform by utilizing social media, namely Instagram. The output of the service is in the form of increased sales, activity videos and the Tiraya platform on Instagram.